Unveiling the anti-cancer mechanisms of calotropin: Insights into cell growth inhibition, cell cycle arrest, and metabolic regulation in human oral squamous carcinoma cells (HSC-3) - Selvaraj Jayaraman; Sathan Raj Natarajan; Vishnu Priya Veeraraghavan; Sharmila Jasmine (Journal of Oral Biology and Craniofacial Research)
Background: Calotropin, a cardiac glycoside obtained from the plant Calotropis gigantea, has demonstrated promising potential as an anti-tumorigenesis compound. Objective: The main objective of this study was to investigate the potential anti-cancer properties of calotropin against HSC-3 oral squamous cancer cells and to elucidate the underlying mechanisms involved in its action. Material and method: Calotropin were treated in HSC-3 to evaluate cell viability by MTT assay. Flow cytometry analysis divulged that calotropin G0/G1 phase cell cycle arrest and apoptosis in HSC-3 cells. Calotropin displayed inhibitory properties against aerobic glycolysis, a metabolic alteration using glucose uptaken, lactose production and LDHA activity assays. Furthermore, migration and invasion assays help that calotropin has ability to reduce the migratory and invasive of HSC-3 cells, using transwell and Matrigel assay. Validation of mRNA expression through RT-PCR. Molecular docking was implemented to validate the binding association of calotropin with apoptosis and metastatic regulating targets. Result: The results exemplify that increasing doses of calotropin effectively hold back the HSC-3 cell progression. Migration and invasion assays help that calotropin has ability to reduce the migratory and invasive of HSC-3 cells, indicating its potential to inhibit cancer metastasis. These results imply that calotropin may influence genes linked to metastasis and apoptosis in order to achieve its beneficial effects on cancer. Docking results provided further support, showing a high binding energy between calotropin and metastasis-mediated pathways. Conclusion: Overall, our findings shed an experimental evidence on how calotropin inhibits the HSC-3 oral squamous cancer cell growth, highlighting the drug's potential as a treatment for oral cancer. Further, investigation on in-vivo experiment is warranted to explore its potential mechanism of action and to develop a novel drug towards clinical trial.